MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
Menu
harshit agarwal Grade: 12
        

f:R→R  f((x-y)2)= (f(x))2 -2xf(y) +y2 then f(x)=?

7 years ago

Answers : (1)

mycroft holmes
266 Points
										

Setting x = y = 0, we get f(0) = f2(0) which means f(0) = 0 or f(0) = 1


 


Swapping x and y we get


 


f[(y-x)2] = f[(x-y)2] = f2(y) - 2y f(x) + x2


 


Hence we get f2(x) - 2x f(y) + y2 = f2(y) - 2y f(x) + x2


 


Now putting y = 0, we get f2(x) - 2x f(0)  = f2(0) - x2


 


If f(0) = 0, then f2(x) = x2 and we get f(x) = x after discarding f(x) = -x as extraneous


 


Likewise, if f(0) = 1, then f(x) = x+1 satisfies the given equation

7 years ago
Think You Can Provide A Better Answer ?
Answer & Earn Cool Goodies
  • Complete JEE Main/Advanced Course and Test Series
  • OFFERED PRICE: Rs. 15,900
  • View Details
Get extra Rs. 3,180 off
USE CODE: CART20
Get extra Rs. 466 off
USE CODE: CART20

Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!! Click Here for details